Consumer Ethnocentrism as Mediator Between Religiosity and Animosity on Starbucks Boycott Motivation - Seprila Putri Firadani; Moch Rizal; Lela Nurlaela Wati (International Journal of Emerging Issues in Islamic Studies, 2025)
Increasing public awareness of social and political issues, as well as the link between certain products and political affiliation, is important for understanding how psychological factors can influence consumption behavior. This research aims to analyze the role of consumers' ethnosentiment in mediating the influence of religiosity and consumers' animosity to boycott motivation on Starbucks products in Jakarta. The methodology used in this study is descriptive and quantitative. using the SEM-PLS methodology with sample data of 230 respondents through the distribution of questionnaires. The results show that religiosity and consumers' animosity direct influence on boycott motivation, and consumers' ethnocentrism can mediate the influence of Religiosity and consumers' animosity on boycott motivation in Jakarta. This research is limited to Starbucks consumers in Jakarta and only analyzes psychological factors to analyze consumer behavior in carrying out boycotts. These results demonstrate the significance of considering psychological and social aspects when examining customer behavior and its effects on the business and society as a whole. shows that businesses must consider the social and political effects of their practices and comprehend the attitudes and beliefs that drive consumers to boycott.